MONUMENTAL AND DECORATIVE PAINTING, ITS FUNCTIONS AND SIGNIFICANCE IN THE URBAN ENVIRONMENT - Irina Tatatrintseva (Innovate Conferences, 2025)
Monumental painting is a form of artistic creativity that involves the creation of large pictorial compositions, often on the walls or ceilings of buildings. This genre of art is usually of a social nature and is associated with important events, cultural or historical themes. Monumental painting can be done in various techniques, such as fresco, mosaic and stained glass.
Keywords: monumental painting, monumental and decorative painting, monumental art, urban environment, synthesis of arts, contemporary art.